Peran Digital Marketing bagi Pelaku UMKM di Kota Medan - Rahmah, Azizah; Nawawi, Zuhrinal M. (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Digital marketing plays an important role for SMEs in Medan City. Digital marketing is a marketing technique that utilizes social media networks such as marketplaces to increase the productivity of MSME actors in the city of Medan. The purpose of the study was to determine the extent of the role of digital marketing for SMEs in Medan City. This study uses a qualitative method with data collection through a literature study taken from previous research. The careful results obtained by MSME actors in Medan City do not fully understand the world of digital marketing, therefore it is necessary for the Medan City Government and the Cooperative Service to provide training or socialization regarding the importance of the role of digital marketing for MSME actors in Medan City to be able to compete at home and abroad